Specificities of Administrative Dispute and Constitutional Complaint Procedure - Manojlović, Savo D (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
The paper explores the unique characteristics of two important legal institutes: administrative lawsuits and constitutional complaints. Although these legal mechanisms can be generally described, their application in practice requires a nuanced understanding that goes beyond mere theoretical knowledge. The aim of the paper is to deepen both theoretical and practical understanding of these institutes by analyzing their specific internal structures, which distinguish them from other legal remedies. The main thesis of the paper is supported by three sub-theses, highlighting the specificities of the procedures initiated by administrative lawsuits and constitutional complaints. These include their supra-institutional character, the subject of control, and the depth of analysis conducted during the decision-making process. The paper particularly focuses on legal systems where centralized administrative and constitutional courts function as separate institutions, while also considering systems where these functions are dispersed within the general judiciary. The conclusion of the paper is that the administrative lawsuit, which historically precedes the constitutional complaint, shares significant "legal DNA" with it, making them distinct from other legal remedies and procedures. This connection underscores the administrative lawsuit as a precursor to the constitutional complaint in systems with centralized constitutional courts.